Migration of cations induces reversible performance losses over day/night cycling in perovskite solar cells. Issue 2 (18th January 2017) - Domanski, Konrad; Roose, Bart; Matsui, Taisuke; Saliba, Michael; Turren-Cruz, Silver-Hamill; Correa-Baena, Juan-Pablo; Carmona, Cristina Roldan; Richardson, Giles; Foster, Jamie M.; De Angelis, Filippo; Ball, James M.; Petrozza, Annamaria; et al.
Abstract : Perovskite cells benefit from a good night's sleep. Abstract : Perovskites have been demonstrated in solar cells with a power conversion efficiency of well above 20%, which makes them one of the strongest contenders for next generation photovoltaics. While there are no concerns about their efficiency, very little is known about their stability under illumination and load. Ionic defects and their migration in the perovskite crystal lattice are some of the most alarming sources of degradation, which can potentially prevent the commercialization of perovskite solar cells (PSCs). In this work, we provide direct evidence of electric field-induced ionic defect migration and we isolate their effect on the long-term performance of state-of-the-art devices. Supported by modelling, we demonstrate that ionic defects, migrating on timescales significantly longer (above 10 3 s) than what has so far been explored (from 10 −1 to 10 2 s), abate the initial efficiency by 10–15% after several hours of operation at the maximum power point. Though these losses are not negligible, we prove that the initial efficiency is fully recovered when leaving the device in the dark for a comparable amount of time. We verified this behaviour over several cycles resembling day/night phases, thus probing the stability of PSCs under native working conditions. This unusual behaviour reveals that research and industrial standards currently in use to assess the performance and the stability of solar cells need to be adjusted for PSCs. Our work paves the way for much needed new testing protocols and figures of merit specifically designed for PSCs.